Competitive effort and employment determination with team production - Jon Strand (University of Oslo, Department of Economics, 2000)
We study a labor market where worker's disutilities of effort differ, firm's outputs depend on the joint efforts of many workers, and individual worker characteristics cannot be observed or inferred by firms. Under assumptions similar to those in Holmström (1982), we demonstrate that an efficient effort allocation then in principle can be implemented by firms paying the same wage to all workers, and more productive workers putting up greater efforts than less productive ones. When the labor market is competitive, however, a first best cannot be implemented due to worker adverse selection. When there are two types of workers and the fraction of the “bad” type is not too high, a competitive equilibrium implies that all worker's productivities are below first best, and that there may or may not be full employment, with possible unemployment evenly distributed among the two types. When the share of “bad” workers is greater, some (or even all) firms attract bad workers only, and unemployment disproportionately borne by the high-productivity type.
Keywords: 330; Vergütungssystem; Arbeitsproduktivität; Leistungsorientierte Vergütung; Gruppenarbeit; Adverse Selection; Theorie